2020
DOI: 10.3390/ijms21207718
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Thyroid Calcification

Abstract: In thyroid cancer, calcification is mainly present in classical papillary thyroid carcinoma (PTC) and in medullary thyroid carcinoma (MTC), despite being described in benign lesions and in other subtypes of thyroid carcinomas. Thyroid calcifications are classified according to their diameter and location. At ultrasonography, microcalcifications appear as hyperechoic spots ≤ 1 mm in diameter and can be named as stromal calcification, bone formation, or psammoma bodies (PBs), whereas calcifications > 1 mm are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 138 publications
(149 reference statements)
0
19
0
Order By: Relevance
“…According to Weiskopf et al [32], an age-related decline in immune functions could affect the capacity of the immune system to respond to pathogens and repair damaged tissue. Macrocalcification is defined as calcifications >1 mm with posterior acoustic shadows [33]. Our results showed that the larger the calcification, the less likely is the complete ablation zone disappearance in the first year.…”
Section: Discussionmentioning
confidence: 60%
“…According to Weiskopf et al [32], an age-related decline in immune functions could affect the capacity of the immune system to respond to pathogens and repair damaged tissue. Macrocalcification is defined as calcifications >1 mm with posterior acoustic shadows [33]. Our results showed that the larger the calcification, the less likely is the complete ablation zone disappearance in the first year.…”
Section: Discussionmentioning
confidence: 60%
“…[ 6 , 7 ] Meanwhile, calcification may be an external manifestation of some diseases, such as papillary thyroid carcinoma and necrotic adipose tissue and so on. [ 8 , 9 ] In addition, calcification occurred in gastric adenocarcinoma, and the cause is related to the parathyroid hormone secreted by adenocarcinoma. [ 10 , 11 ] However, up to now, there are few reports about calcification associated with GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of psammoma bodies is still controversial with theories involving vascular thrombosis of papillae, followed by calcification and endothelial necrosis. More recently, osteopontin (OPN), a calcium-binding glycophosphotein has been implicated in the formation of psammoma bodies being expressed in CD68 positive macrophages along with other factors that include alkaline phosphatase, osteocalcin, metalloproteinases, bone sialoprotein, and others [56]. OPN expression has been shown to be increased in meningiomas compared to normal meninges, correlates with histological grade, and is a predictor of recurrence in WHO grade I tumors [57,58].…”
Section: Meningothelial Meningioma Of the Mastoid Presenting With Tinnitus In A 46-year-old Woman No Connection To The Cns Was Seen By Immentioning
confidence: 99%